Pandangan Ulama Tentang Larangan Menyentuh dan Membaca Al-Qur’an dalam Keadaaan Haid - Hanik Latifah; Dzin Nun Naachy (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2023)
Background. This research focuses on aspects of prohibitions for women during menstruation from the views of ulama. As is known, the commentators have not provided sufficient studies on the various implications arising from the existence of this menstrual cycle except for a global explanation of all taboos and prohibitions for menstruating women. Including touching and reading the Koran, this article focuses on aspects of prohibitions for women in reading the Koran during menstruation from the perspective of the ulama. Methods. The method used in this writing is the literature method with a normative approach. This approach is then analyzed descriptively starting from data description, data formulation and data interpretation. Results. Based on the results of the study, some of the scholars' views regarding reading the Koran during menstruation are permissible, some are not. Imam Syafi'i and Imam Hambali consider that women who are menstruating are prohibited from reading the Koran unless they are not intending to read the Koran as a recitation of the Koran, only as dhikr or for teaching. Meanwhile, Imam Maliki considers that reading the Koran for menstruating women is absolutely permissible.